Highly efficient magnetic resonance coupling wireless power transfer for 5G applications - Kamarudin, Saidatul Izyanie (2021)
This thesis reviewed the existing technology of the WPT system. Most Magnetic Resonance Coupling Wireless Power Transfer (MRC WPT) applications have been designed in kHz and MHz frequency spectrum. The International telecommunication Union has declared the following spectrum for 5G communication, and the spectrum range is; 3.4-3.6 GHz, 5-6 GHz, 24.25-27.5 GHz, 37-40.5 GHz, and 66-76 GHz frequency bands. The proposed design is first analyzed theoretically in MATLAB to realize the highly efficient MRC WPT at GHz frequency band. The Planar Spiral Coil Magnetic Resonance Coupling (PSC MRC) Antennas are designed at 3.4-3.5 GHz, and 5-6 GHz frequency band for the Circular and Square shapes with one, two and three turns. The PSC MRC Antennas circumference is designed to the one-wavelength loop λ. The Antenna will resonate when C is slightly larger than λ. The mutual coupling M has been calculated as the mutual coupling is crucial in determining the efficiency of the MRC WPT system,. and the From the results, the PSC MRC Circular one-turn of 3.4- 3.5 GHz has the best mutual coupling, M at the distance of 0 to 20 mm. while the PSC MRC of square two-turns is the highest mutual coupling, M when the distance is more than 20 mm amongst the other PSC MRC designs. Also, the theoretical efficiency of the proposed PSC MRC Antennas is also calculated in MATLAB. For the 3.4-3.5 GHz designed, theoretically, the PSCMRC Circular's efficiency is better than the PSC MRC Square design's efficiency. For the 5-6 GHz PSC MRC design, the Square-one-turn has the highest efficiency than the Circular one-turn designs. Next, all the designs have been simulated in the CST software to compare with the theoretical results. The PSC MRC Antennas are modelled on the FR4 substrate with thickness and copper thickness of 0.6 mm and 0.035 mm, respectively, in the CST Software. The parametric evaluation has been done in CST software to find the best performance of S11 (dB) and SRF (GHz) of the proposed PSC MRC Antenna designs to be working at a 5G frequency band. The return loss S11 of each design needs to be below -10 dB to improve the efficiency of the MRC WPT system. In conclusion, all the PSC MRC Antenna for the circular and square designs at 3.4-3.5 GHz and 5-6 GHz are designed to be operated below -10 dB of return loss S11. Finally, the Circular PSC MRC Antenna one-turn, two-turns, three-turns at 3.4-3.5 GHz and Circular one-turn PSC MRC Antenna 5-6 GHz are fabricated because they gave the best results when comparing with the theoretical and simulation results. The measurements results are compared with the simulated and the theoretical results to analyzed the efficiency performance with the distance,d. From the measurement results, the highest efficiency for the proposed PSC MRC Antenna design is the Circular one-turn PSC MRC Antenna at 3.4-3.5 GHz. The PSC MRC antenna's efficiency is 31.58 % when the distance is 2 mm, 31.26% and 31.02% when the distance is 3 mm and 4 mm, respectively. It can be concluded that, previously, most PSC MRC Antenna designs are only used for short-distance low frequency and CMOS applications. Strong near-field PSC MRC antenna structures are designed at a 5G frequency band has been obtained, which offers overall efficiency higher than 20%, close to 7 mm distance by generating an intense magnetic field around the loop coil antenna. The efficiency in CMOS applications is also lower than 20%.